Analisis Rangkaian Komparator dengan Variasi IC Op-Amp yang Tersedia pada Circuit Wizard - Gita Alisrobia; Hani Nur Asri; Makna A’raaf Kautsar; Muhammad Satrio Dwi Utomo; Muntaha Hasanah; Vina Fujiyanti (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
This research was conducted on the Circuit Wizard simulator application to simplify the students, especially in the field of Telecommunications Systems, Indonesia Education University, Purwakarta for understanding of the characteristics of each Operational Amplifier with a comparator circuit. In addition, this article presented and tested a comparator circuit to compare the results of two voltages, namely inverting and non-inverting Op Amps. The method used in the research, by making a comparator circuit with 10 different types of Operational Amplifiers. This is carried out to get more valid comparison result and the simulation is run for six times. The simulation was conduct in two comparison conditions with a Vin(+) value of 6V, a predetermined Vin(-) value and a DC voltage flowing of 12V. The results of the analysis through simulations with 10 types of Operational Amplifiers produced different outputs. In principle, it can be influenced by V rail-to-rail, intrinsic circuit, Zin, Zout, Pin and the different characteristics of each Operational Amplifier model. As a comparison, based on its characteristics, the LM741 data sheet has a value of Vs = ±15 V (output voltage swing) if RL 10 kΩ and RL 2kΩ. Whereas in the data sheet LM258 has a value of VS = 30 V if RL = 2 kΩ, VS = 30 V if RL 10 kΩ, VS = 5 V if RL 2 kΩ for positive rail, and VS = 5 V if RL 10 kΩ for negative rails. It can be concluded that the Circuit Wizard software makes it easy to simulate the comparator circuit, so it suggested to be simulated on other materials.